2017
DOI: 10.1590/2359-3997000000270
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the effects of irisin levels in HIV-infected subjects: correlation with adiposity, fat-free mass, and strength parameters

Abstract: Objective: Patients infected with the human immunodeficiency virus (HIV) have an increased risk of metabolic disorders and alterations on irisin levels. Therefore, the purpose of the current investigation was to quantify the circulating irisin concentration in HIV-infected subjects under highly active antiretroviral therapy and to determine possible correlations between irisin levels with fat mass, fat-free mass, body mass index (BMI), and muscle strength. Subjects and methods: Cross-sectional study of 10 men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(37 reference statements)
2
4
1
Order By: Relevance
“…It is worth noting that, although it was not evaluated in the present study, the body composition modifications characteristic of lipodystrophy can compromise muscle mass, besides contributing to metabolic and cardiovascular alterations 8,11 . The low relative handgrip strength found mainly in women with HIV/AIDS matches the results of a Brazilian study by Trombeta et al 12 . that showed higher relative handgrip strength in men (0.59 kg of strength/kg of body weight) than in women (0.48 kg of strength/kg of body weight).…”
supporting
confidence: 89%
“…It is worth noting that, although it was not evaluated in the present study, the body composition modifications characteristic of lipodystrophy can compromise muscle mass, besides contributing to metabolic and cardiovascular alterations 8,11 . The low relative handgrip strength found mainly in women with HIV/AIDS matches the results of a Brazilian study by Trombeta et al 12 . that showed higher relative handgrip strength in men (0.59 kg of strength/kg of body weight) than in women (0.48 kg of strength/kg of body weight).…”
supporting
confidence: 89%
“…The average handgrip strength of the respondents was 20.58±10.60 kg. This is not in line with earlier studies on HIV outpatients in Brazil, which found that the average handgrip strength of patients' right hands was 39.05±11.88 kg and the average of their left hands was 35.40±10.53 kg (Trombeta et al, 2017). There are several factors that may have led to this difference in results, such as the difference in patient criteria and the method used to measure handgrip strength.…”
Section: Hiv and Aids Inpatient's Body Mass Index And Handgrip Strengthcontrasting
confidence: 80%
“…There are several factors that may have led to this difference in results, such as the difference in patient criteria and the method used to measure handgrip strength. In Trombeta et al (2017) study, the respondents were outpatients, while, in the current study, they were inpatients. In the current study, handgrip strength was measured with patients in a sitting position on the edge of their bed; in the earlier study, the measurements were carried out in a standing position.…”
Section: Hiv and Aids Inpatient's Body Mass Index And Handgrip Strengthmentioning
confidence: 82%
“…32,33 These alterations are known to have a negative impact on lean mass and, consequently, on muscle strength. 18,34 In the present study, two pathways related to the understanding of HGS with body composition were verified: the first shows that the greater the lean mass, the greater the HGS; the second points to an inversely proportional principle, in which the greater the values of BMI, abdominal circumference, sum of skinfolds, percentage of fat, and fat mass, the lower the HGS. This response pattern is not limited to body composition; biochemical indicators such as total cholesterol, when altered, are also related to a lower HGS, as seen in the present study and confirmed by Santos et al 15 Thus, as muscle strength is an important component of health-related physical fitness, changes in body composition that reduce muscle strength directly impact the performance of activities of daily living and the functional capacity of people living with HIV.…”
Section: Discussionsupporting
confidence: 59%